Self-triggered conformations of disulfide ensembles in coordination polymers with multiple metal clusters1. Issue 14 (14th April 2015) - Tseng, Tien-Wen; Luo, Tzuoo-Tsair; Shih, Ying-Ru; Shen, Jing-Wen; Lee, Li-Wei; Chiang, Ming-Hsi; Lu, Kuang-Lieh
<x xml:space="preserve">Abstract</x> Five coordination polymers containing manganese(ii) ions, 6, 6′-dithiodinicotinate, and/or N-donor coligands display mononuclear, trinuclear cluster and polymeric metal oxide wire and exhibit intrinsic biomimetic characteristics.